Efficacy and Safety 48 Weeks after Switching from Efavirenz to Rilpivirine Using Emtricitabine/Tenofovir Disoproxil Fumarate–Based Single-Tablet Regimens. Issue 5 (September 2013) - Mills, Anthony M.; Cohen, Calvin; DeJesus, Edwin; Brinson, Cynthia; Williams, Scott; Yale, Kitty L.; Ramanathan, Srini; Wang, Maggie H.; White, Kirsten; Chuck, Susan K.; Cheng, Andrew K.
Abstract : Background: Due to ongoing neuropsychiatric adverse events in some efavirenz (EFV)-treated patients, a switch to an alternative non-nucleoside reverse transcriptase inhibitor may be considered. Rilpivirine (RPV) has been coformulated as a single-tablet regimen (STR) with emtricitabine/tenofovir disoproxil fumarate (FTC/TDF), and the components have demonstrated noninferior efficacy to EFV+FTC/TDF, good tolerability profile, and high adherence. After discontinuation, EFV has an extended inductive effect on cytochrome P450 (CYP) 3A4 that, after switching, may reduce RPV exposures and adversely impact clinical outcomes.Objective: This study examines the clinical implications of reduced RPV exposures with concomitant FTC/TDF and declining EFV exposures when patients, intolerant to EFV, switch from EFV/FTC/TDF to RPV/FTC/TDF.Methods: This 48-week, phase 2b, open-label, multicenter study evaluated the efficacy and safety of switching from EFV/FTC/TDF (≥3 months duration) to RPV/FTC/TDF. Virologic suppression (HIV-1 RNA <50 copies/mL), safety, and EFV and RPV pharmacokinetics were assessed.Results: At weeks 12 and 24, all 49 dosed subjects remained suppressed on RPV/FTC/TDF. At week 48, 46 (93.9%) subjects remained suppressed and virologic failure occurred in 2/49 (4.1%) subjects with no emergence of resistance. EFV concentrations were above the 90th percentile for inhibitory concentration (IC90 ) for several weeks after EFV discontinuation, and RPV exposures were in the range observed in phase 3 studies by approximately 2 weeks post switch. No subjects discontinued the study due to an adverse event.Conclusions: Switching from EFV/FTC/TDF to RPV/FTC/ TDF was a safe, efficacious option for virologically suppressed HIV-infected patients with EFV intolerance wishing to remain on an STR.